Comparison Between Amide Proton Transfer Magnetic Resonance Imaging Using 3-Dimensional Acquisition and Diffusion-Weighted Imaging for Characterization of Prostate Cancer: A Preliminary Study. Issue 2 (13th March 2023) - Kido, Ayumu; Tamada, Tsutomu; Ueda, Yu; Takeuchi, Mitsuru; Kanki, Akihiko; Yamamoto, Akira
Abstract : Objective: This study aimed to compare diagnostic performance for tumor detection and for assessment of tumor aggressiveness in prostate cancer (PC) between amide proton transfer magnetic resonance imaging (MRI) with 3-dimensional acquisition (3DAPT) and diffusion-weighted imaging. Methods: The subjects were 23 patients with 27 pathologically proven PCs who underwent 3T multiparametric MRI. With reference to the pathology findings, 2 readers in consensus identified the location of PC on multiparametric MRI and measured APT signal intensity (APT SI [%]) and mean apparent diffusion coefficient (ADC) of the benign region and each PC lesion. Results: The mean ADC showed a significant difference between benign regions and PC lesions (0.74 ± 0.15 vs 1.37 ± 0.21, P < 0.001), whereas APT SI did not ( P = 0.091). Lesion APT SI was significantly higher and lesion ADC was significantly lower in PCs with Gleason group (GG) ≥3 than in PCs with GG ≤2 (3.37 ± 1.30 vs 1.78 ± 0.67, P < 0.001, and 0.71 ± 0.18 vs 0.79 ± 0.10, P = 0.038, respectively). The APT SI was significantly higher in GG3 than in GG1, in GG3 than in GG2, and in GG4 than in GG2 ( P = 0.009, P = 0.001, and P = 0.006, respectively). The area under the curve for separating tumor lesions and benign regions was 0.601 for 3DAPT and 0.983 for ADC ( P < 0.001). The area under the curve for separating tumors with GG ≤2 from tumors with GG ≥3 was 0.912 for 3DAPT and 0.734 for ADC ( P = 0.172). Conclusions: In patients with PC, it might be preferable to use ADC to discriminate benign from malignant tissue and use APT SI for assessment of tumor aggressiveness.